Evaluasi Revitalisasi Pasar Rakyat Bung Karno Wonogiri - Hutami Kanthi Shashanty; Ismi Dwi Astuti Nurhaeni (Jurnal Administrasi Publik, 2023)
Nowadays the existence of traditional markets is beginning to be eroded by the existence of modern markets which have a better image in the eyes of the public. Revitalization is carried out by the government as an effort to promote traditional markets. One of the revitalized markets is Bung Karno Wonogiri Market. This study aims to evaluate the revitalization of the Bung Karno Market in Wonogiri Regency in 2017 in terms of input, process, output, and outcomes dimensions based on Bridgman and Davis’s policy evaluation theory. The results of the study found that the input for revitalization in the form of human resources was sufficient in quality and quantity, but the revitalization funds were considered insufficient and too late. The revitalization process has been effective and quite efficient, marked by clear targets, repeated socialization, there are revitalization objectives, and monitoring of revitalization. The output dimension has met the target, which is right on target, covering all Bung Karno Market traders, but not all traders are involved in the revitalization. The revitalization output is in the form of changes to facilities that fulfill around 82 percent of facilities in accordance with regional regulations, zoning, additional contract workers, e-retribution, and online markets. The outcome of the revitalization is that the market becomes clean and orderly which has an impact on the surrounding traffic, the turnover of traders has increased, and has decreased due to the Covid-19 pandemic.